2021
DOI: 10.1101/2021.06.28.21259532
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Polygenic risk for psychiatric disorder reveals distinct association profiles across social behaviour in the general population

Abstract: Many complex psychiatric disorders are characterised by a spectrum of social difficulties. These symptoms lie on a behavioural dimension that is shared with social behaviour in the general population, with substantial contributions of genetic factors. However, shared genetic links may vary across psychiatric disorders and social symptoms. Here, we systematically investigate heterogeneity in shared genetic liabilities with attention-deficit/hyperactivity disorder (ADHD), autism spectrum disorders (ASD), bipolar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…However, the strength of association and the agerelated increases depended on the specific disorder considered. Similarly, Schlag et al (2021) found differential effects of PGS for psychiatric traits on social behavioural phenotypes (e.g. peer problems), as well as age-moderated effects, depending on the behavioural problem subtype considered.…”
Section: Heterogeneity and Specificity Across Developmentmentioning
confidence: 80%
See 2 more Smart Citations
“…However, the strength of association and the agerelated increases depended on the specific disorder considered. Similarly, Schlag et al (2021) found differential effects of PGS for psychiatric traits on social behavioural phenotypes (e.g. peer problems), as well as age-moderated effects, depending on the behavioural problem subtype considered.…”
Section: Heterogeneity and Specificity Across Developmentmentioning
confidence: 80%
“…Similarly, Schlag et al. (2021) found differential effects of PGS for psychiatric traits on social behavioural phenotypes (e.g. peer problems), as well as age‐moderated effects, depending on the behavioural problem subtype considered.…”
Section: Applications To Longitudinal Designsmentioning
confidence: 83%
See 1 more Smart Citation